On-ground demonstration of laser-link construction for space-based detection of gravitational waves - Gao, Ruihong; Wang, Yikun; Cui, Zhao; Liu, Heshan; Liu, Anwei; Qian, Xingguang; Wang, Xue; Yao, Zhixiong; Yang, Qiujie; Jia, Jianjun; Qi, Keqi; Wang, Shaoxin; et al. (Optics and lasers in engineering, 2023)
•An experimental system is established to simulate the whole laser link construction process in space-based gravitational wave detection.•We comprehensively considered the simulation of actual optical system, actual process and critical working condition.•The on-ground acquisition precision as well as the laser pointing precision can fulfill the requirement.•We fully verify the feasibility of the proposed three-stages link construction scheme and resolve the relevant technique problems based on experimental method. Laser acquisition and pointing system is subject to establish a 106km magnitude inter-satellite laser link with ultra-high pointing precision of 10 nrad/Hz (1 mHz-1 Hz) in space-based gravitational wave detection missions. For the unprecedented challenge, a dedicated laser link construction scheme with three different detectors is proposed. After initial pointing with star trackers, CMOS/CCD cameras intend to suppress the laser pointing error to 1 μrad. QPDs are subsequently used to achieve the final requirement. With various detectors and technologies, the scheme need intensive verification and study. We first design and build an on-ground laser link construction experimental system, which can simulate the whole process and recreate the actual critical working condition as realistic as possible by comprehensively considering the simulation of optical system, far field beam receiving characteristics and target precision. Results are well in agreement with the requirements and confirm the scheme under realistic conditions, which have not yet been fully tested experimentally.